A Continuity of Care Approach in Managing Grade II Hyperemesis Gravidarum During Pregnancy: A Case Study at an Independent Midwifery Practice in North Sumatra, Indonesia - Deli Putriani Nasution; Ribur Sinaga; Riska Susanti Pasaribu; Kamelia Sinaga; Desna Elfita (Jurnal Ners, 2026)
Background: Continuity of Midwifery Care (CoMC) is a woman-centered approach that provides integrated and continuous care throughout pregnancy, childbirth, the postpartum period, newborn care, and family planning. Hyperemesis gravidarum is a severe pregnancy-related condition characterized by persistent nausea and vomiting that may lead to dehydration, nutritional deficiencies, and adverse maternal and fetal outcomes if not appropriately managed. Objective: This study aimed to describe the implementation of Continuity of Midwifery Care for a pregnant woman diagnosed with Grade II hyperemesis gravidarum at an independent midwifery practice in Medan, North Sumatra, Indonesia. Methods: A descriptive case study design was employed. Comprehensive midwifery care was provided using the seven-step Helen Varney midwifery management framework and documented through the Subjective, Objective, Assessment, and Plan (SOAP) approach. The continuity of care covered antenatal care, labor and delivery, postpartum care, newborn care, and family planning services. Results: The client was diagnosed with Grade II hyperemesis gravidarum at 20 weeks of gestation and received comprehensive antenatal management through four antenatal care visits. The pregnancy progressed without major complications following appropriate midwifery interventions. The client delivered a healthy female infant through spontaneous vaginal birth on February 8, 2026. During the postpartum period, both mother and newborn remained in good health, breastfeeding was successfully established, and the mother selected the Lactational Amenorrhea Method (LAM) as postpartum contraception. No significant maternal or neonatal complications were identified throughout the continuum of care. Conclusion: The implementation of Continuity of Midwifery Care contributed to optimal maternal and neonatal outcomes in this case of Grade II hyperemesis gravidarum. The care provided was consistent with established midwifery management principles, and no discrepancies were identified between theoretical guidelines and clinical practice. This case highlights the importance of continuous, comprehensive, and individualized midwifery care in improving maternal and newborn health outcomes.